Desenvolvimento de método de geração termoquímica de vapor assistida por radiação infravermelha para determinação de mercúrio por espectrometria de absorção atômica - Campos, Victor Marques (2024)
A simple, low-cost and easy-to-implement system using infrared radiation for thermochemical vapor generation (TVG) coupled to atomic spectrometry was developed for the analysis of mercury species in certified reference materials and in marine sediment samples. Two thermochemical reactors were designed and assembled using infrared lamps to generate heating in the TVG system. The first reactor was proposed and used for the thermochemical vapor generation (TVG) of inorganic species and methyl mercury by heating biological samples, without and with the addition of hydrogen peroxide, respectively, at temperatures from 165 to 285ºC. The power of the infrared lamp (1000 W) was controlled with a dimmer to adjust the reactor temperature, measured with the use of a thermocouple. A quartz capillary was used to flow the sample through the TVG reactor. The impacts of the concentration of formic acid and hydrogen peroxide, temperature and flow of carrier gas (N2) were evaluated in the system on the response of inorganic mercury and methyl mercury, in order to identify the optimal conditions for the thermochemical vapor generation. The accuracy of the method was validated using the certified reference materials NIST 1641d (water), DORM 1 (fish protein) and DOLT-3 (dogfish liver) obtaining a detection limit of 0.41 µg kg-1. The second TVG reactor was built to develop a method for analyzing the total mercury content in samples of marine sediments contaminated in the oil spill (crude oil) on the coast of Ceará in 2019. The TVG reactor was assembled with an infrared lamp (500 W) with system power and temperature controller. A PFA capillary tubing was placed around the lamp through which the sample was flowed. The accuracy of the method was assessed using PACS-2 certified reference material (marine sediment) obtaining a result of 3.2 ± 0.10 mg Kg-1 obtaining a result of 3.2 ± 0.10 mg Kg-1. The developed method was applied to determine the total mercury content in marine sediment samples collected on beaches in the State of Ceará. Mercury concentrations ranged from 0.41 to 0.95 mg kg−1 in the analyzed samples